Temporal and Spatial changes of phytoplankton in North Coastal water of Lattakia. - Alakash, Ranim; Feirouz Darwish (Latakia University Journal -Biological Sciences Series, 2022)
This research was carried out on the coastal waters of (Burj Islam, Wadi Qandil, and Umm al-Tuyour) as a complement to the previous studies along the Syrian coast. Six stations were selected based on their different environmental characteristics, and their continuous exposure to sources pollution (sewage – human activities). Six cruises were carried out during the study period, which lasted from June 2020 until June 2021. Water samples were collected for analysis and determine the concentrations of chlorophyll (a), Phytoplankton abundance and its specific composition, which collected, in addition to field measurements of some physical and chemical factors (temperature - salinity -PH ). The registered concentrations are ranged between 0.0 – 6.7 mg /m3 for chlorophyll (a). Values of the total abundance ranged between 725 -550122 cell/L. This study has recorded) 87(species of phytoplankton in study sites, distributed as follow: (63) species of Diatoms, (19) species of Dinoflagellates, (3) species of Chlorophyta, and 2 species of Cyanophyta.